2006
DOI: 10.3171/spi.2006.5.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Primary intradural extraarachnoid Hodgkin lymphoma of the cervical spine

Abstract: ✓ This 42-year-old man presented with an intradural extramedullary mass in his lower cervical spine. On imaging studies the lesion mimicked the appearance of a meningioma. At surgery, the mass was found to be an intradural extra-arachnoid tumor. An intraoperative pathological examination determined the lesion to be a Hodgkin lymphoma. The procedure was limited to biopsy sampling and the patient was treated further with adriamycin, bleomycin, vincristine, and dacarbazine chemotherapy, after which remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Higgins & Peschel reported variable incidence of 1.15-7.6% for the spinal cord compression caused by epidural HL [5]. on literature research, we could find only six reports on primary HL of the spinal canal [5][6][7][8][9][10], out of which only one was intradural in the cervical region [10], leaving behind the rest in the extradural space. This is the second case report of primary intradural HL and the first case to involve the lower lumbar and sacral spine by this entity.…”
Section: Discussionmentioning
confidence: 81%
“…Higgins & Peschel reported variable incidence of 1.15-7.6% for the spinal cord compression caused by epidural HL [5]. on literature research, we could find only six reports on primary HL of the spinal canal [5][6][7][8][9][10], out of which only one was intradural in the cervical region [10], leaving behind the rest in the extradural space. This is the second case report of primary intradural HL and the first case to involve the lower lumbar and sacral spine by this entity.…”
Section: Discussionmentioning
confidence: 81%
“…Intra-operative evidence of the dural attachment might be due to its origin from these lymphatic spaces. [2] Histopathology of the tumor was confirmatory of non-Hodgkin's lymphoma. The diagnosis was also confirmed by immunohistochemistry showing CD20 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…in 2006. [2] They operated on a cervical intradural extramedullary lesion which they thought initially as meningioma. After performing a laminectomy, the biopsy of the lesion was in favor of Hodgkins lymphoma; hence, the surgery was abandoned and the patient subsequently received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 2 reports have documented an intradural extramedullary lesion. 1,7 However, in 1 of these 2 cases, whether the tumor was solitary or part of systemic lesions was not clarified. 1 Although Heran et al 7 reported the first case of primary intradural extraarachnoid Hodgkin lymphoma of the cervical spine, mediastinal and paratracheal lymphadenopathies were seen in that case.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 However, in 1 of these 2 cases, whether the tumor was solitary or part of systemic lesions was not clarified. 1 Although Heran et al 7 reported the first case of primary intradural extraarachnoid Hodgkin lymphoma of the cervical spine, mediastinal and paratracheal lymphadenopathies were seen in that case. Thus, the present case is the first instance of presumed solitary intradural extramedullary lymphoma of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%